MODERN PROBLEMS OF CHEMISTRY METHODOLOGY (1950-2000) - Soibnazarova Gulnora Bektemirovna (Journals Park Publishing, 2022)
Since 1917, throughout the twentieth century, general secondary education has been undergoing gradual reform. The need for reforms was due to changing socio-social and ideological factors, which at the first stage included the need to provide students with a certain amount of knowledge, skills and abilities laid down in the subject systematic courses and constituting the foundations of sciences.
Keywords: chemical, teaching, lessons, I,Butlerov, D.A. Epstein, S.A. Shurkhin, K.Ya. Parmenov and A.G. Dubov